1993
DOI: 10.1093/nar/21.15.3391
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of theEscherichia coligenome. III. DNA sequence of the region from 87.2 to 89.2 minutes

Abstract: The DNA sequence of 96.5 kilobases of the Escherichia coli K-12 genome has been determined, spanning the region between rrnA at 87.2 minutes and katG at 89.2 minutes on the genetic map. The sequence includes 84 open reading frames, of which 46 code for unidentified proteins. Six previously mapped but unsequenced genes have been identified in this span: mob, fdhD, rhaD, rhaA, rhaB, and kdgT. In addition, five new genes have been assigned: the heat shock genes hsIU and hsIV, and the genes fdoG, fdoH, and fdoI, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
114
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(120 citation statements)
references
References 55 publications
6
114
0
Order By: Relevance
“…The Nterminal amino acid sequence of protein C coincides with that of L31 (Wada et al 1990). But its C-terminus is eight amino acids longer than that of L31 (Brosius 1978;Plunkett et al 1993). Our recent work has shown that L31 is generated by cleavage of the primary product (C protein) with protease VII, an outer membrane protein, during the grinding or lysis of cells, since a mutant cell (AD202) disrupted in the gene for protease VII (ompT) only has proteinC.…”
Section: Introductionmentioning
confidence: 99%
“…The Nterminal amino acid sequence of protein C coincides with that of L31 (Wada et al 1990). But its C-terminus is eight amino acids longer than that of L31 (Brosius 1978;Plunkett et al 1993). Our recent work has shown that L31 is generated by cleavage of the primary product (C protein) with protease VII, an outer membrane protein, during the grinding or lysis of cells, since a mutant cell (AD202) disrupted in the gene for protease VII (ompT) only has proteinC.…”
Section: Introductionmentioning
confidence: 99%
“…The final step of this biosynthetic pathway requires the mob locus, which encodes functions that catalyze the synthesis of MGD from MPT and a GMP donor, most probably GTP (8). The mob locus in E. coli contains two genes, mobA and mobB, arranged as a single transcription unit (8,9). MobA is a well characterized monomeric enzyme capable of the synthesis of MGD from MPT and GMP, and it has been shown to activate the molybdoenzyme nitrate reductase (10).…”
mentioning
confidence: 99%
“…Sequence analysis of the nt-f gene product revealed sequence similarity to a 18.9-kDa protein encoded by the f170 gene located immediately downstream to the mob locus in E. coli which is also implicated with the biosynthesis of the molybdopterin cofactor (Plunkett et al, 1993).…”
Section: Resultsmentioning
confidence: 99%